2018
DOI: 10.1080/0886022x.2018.1487859
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors analysis for hyperuricemic nephropathy among CKD stages 3–4 patients: an epidemiological study of hyperuricemia in CKD stages 3–4 patients in Ningbo, China

Abstract: Objective: Uric acid (UA) is a risk marker of CKD and SUA level in CKD 3–4 patients closely correlates with hyperuricemic nephropathy (HN) morbidity. This study was designed to evaluate the risk factors for HN in CKD 3–4 patients.Methods: The 461 CKD 3–4 patients were recruited and all patients were divided into three groups (24 h UUA normal, underexeret, and overproduct type groups) according to the 24 h UUA level after receiving low purine food for five days. Clinical and biochemical characteristics of CKD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Hyperuricemia has been widely reported as a risk factor for a variety of kidney diseases ( 14 , 15 ). The observation that hyperuricemia frequently precedes the development of CKD suggests that factors other than renal insufficiency are likely involved in the pathogenesis of the elevation in uric acid ( 16 ). Studies have confirmed that ~2/3 of UA in the human body is reabsorbed and secreted by the renal tubules ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperuricemia has been widely reported as a risk factor for a variety of kidney diseases ( 14 , 15 ). The observation that hyperuricemia frequently precedes the development of CKD suggests that factors other than renal insufficiency are likely involved in the pathogenesis of the elevation in uric acid ( 16 ). Studies have confirmed that ~2/3 of UA in the human body is reabsorbed and secreted by the renal tubules ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both urinary NGAL and KIM-1 excretion levels were significantly elevated compared with those in normal controls. In a large study, Wu et al 35 In contrast, eGFR decline among White patients with hyperuricemia fell from 43.8 + 5.5 to 38.1 + 5.7 mL/min per year resulting in an annualized drop of −2.81 mL/min per year. This difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 93%
“…Compared with normal controls, urinary KIM-1/Cr levels were 3-fold higher in patients with hyperuricemia due to underexcretion, whereas the ratios for patients with uric overproduction were 7-fold higher. 35 The sensitivity of urinary NGAL and KIM-1 in detecting renal tubular injury offers the potential to identify patients with subclinical renal injury, thus increasing the risk of progressive renal disease. MCP-1 is synthesized and excreted by the renal tubular epithelium and endovascular cells, and by infiltrating chronic inflammatory cells under conditions of renal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies postulate the causal role of UA in the progression of renal disease and cardiovascular diseases. Mallat et al and Kuwabara et al have found that hyperuricemia could induce pathological restructuring of vessels and vascular nephrosclerosis, and was associated with the mortality and development of hypertension, cardiovascular diseases, and chronic renal diseases, [25,26] while risk factors for CKD and hyperuricemia include gender, alcohol consumption, BMI and other characteristics [27]. It has been reported recently that soluble UA has important biological roles such as in pro-inflammatory and proliferative effects on vascular smooth muscle cells; induction of the dysfunction of endothelial cells in rats; and in inducing systemic inflammatorome and generation of oxidative stress [28,29].…”
Section: Discussionmentioning
confidence: 99%